Radiofrequency ablation of varicose veins: experience at a tertiary hospital - Ganie, Farooq A; Lone, Ghulam Nabi; Khan, Mohd Yaqoob; Manzoor, Syed Mohsin; Bhat, Mudasir Hamid; Ahmad, Syed Nisar (IMC Journal of Medical Science, 2021)
Background and objectives: Radiofrequency ablation (RFA) is a recent modality of treatment of the affected varicose vein. In the present study, the outcome of great saphenous varicose vein disease treated by radiofrequency ablation technique was analyzed. Methods: Patients with varicosities of the lower limb affecting mainly the great saphenous vein were (GSV) included. The procedures were carried out under spinal anesthesia. The target varicose vein was accessed by Seldinger technique and the RFA catheter advanced 2 to 3 cm below sapheno-femoral junction under ultrasonography (USG) guidance. A tumescent anesthetic infiltration was given in a solution of normal saline and sodium bicarbonate before the vein being ablated. Results: The success rate of RFA was 97.5 % (39 out of 40). One patient showed episodic recanalisation of vein at one year duplex colour scan. Though the complications related to procedure were negligible, one patient developed endovenous heat induced thrombosis (EHIT) and non-fatal pulmonary thromboembolism (PTE) which was managed adequately. Conclusion: Endovenous RFA is a useful treatment modality for varicose vein disease primarily due to great saphenous insufficiency with marked symptomatic improvement and least recurrence. Although the complications are minimal, EHIT is a potential and serious complication of heat ablation. Ibrahim Med. Coll. J. 2021; 15(1): 37-40